Construções geométricas no ambiente virtual de ensino TeleMeios com mediação na Sequencia Fedathi. - Jucá, Adelmir de Menezes (2011)
In this work I evaluated the potentials of a Virtual Teaching Environment – TeleMeios in the development of a distance course about Geometric Constructions using ruler and measure with the teacher practicing his function as a mediator following the guidelines of Fedathi se-quence. The content of Geometric Constructions, despite of its significance, is been insuffi-ciently studied during fundamental teaching in Brazil so I investigated through participatory action research, using the methodology of Didactic Engineering, a new proposal that joined the technologies as a motivator and facilitator element for the work with this theme. Tele-Meios is a telematic environment elaborated with the utilization of free software routines, which has an interface that promotes the communication through text, sound, image and email, incorporating all the resources nowadays utilized on distance education and advances allowing the complete sharing of applicative. The differential of our proposal was the settle-ment of a total interaction between the participants, what happened through a synchronous interconnection, real time, via internet, with all the participants sharing the softwares. This sharing means that all the participants could visualize the activities developed by their part-ners, the processes that were remotely used, which was the utilized method of problem solu-tion and, in addition, they remotely accessed the other participants’ machines, being allowed to write and draw in the computer of a virtual partner. The virtual classes were planned through Didactic Engineering and approached the main elementary geometric constructions as perpendicular, bisectrix, bisector, able arc and others. During the sessions we substitute the traditional ruler and measure and utilized the software of dynamic geometry: GeoGebra. Play-ing my teacher role, I adopted in the interventions the management indicated by Fedathi Se-quence, which is a theoretic-methodological approach created on Multimeios Laboratory of Federal University of Ceará by professor Dr. Hermínio Borges Neto. Through its four steps: positioning, maturation, solution and test, the new methodology aims, from the mediation between teacher and students, to provide a significant learning constructed with the active participation of the students in a collaborative way. From all this theoretical and technological context, the Geometric Construction course was materialized in five classes for five students and it was possible to observe the effectiveness of the technological environment assembled by the strong interaction between the partners and the active mediation of the teacher. The geometric constructions were elaborated in partnership through the participation of all mem-bers of the group.